2020
DOI: 10.7759/cureus.9250
|View full text |Cite
|
Sign up to set email alerts
|

Association of Somatic Symptom Severity With Sociodemographic Parameters In Patients With Medically Unexplained Physical Symptoms: A Cross-Sectional Study From a Tertiary Care Center in India

Abstract: Baitha et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
2
8
0
1
Order By: Relevance
“…According to the literature [ 32 , 36 , 37 ], women generally report more bodily distress and more frequent somatic symptoms than men, and depressive and anxiety disorders are more prevalent in women as well. Studies on somatic symptoms have mentioned the influence of educational level [ 10 , 13 , 14 , 22 ], but the importance of this factor remains unexplored. Although the findings of this study suggest a possible association between these variables (gender and educational level) and the FSS, it must be confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the literature [ 32 , 36 , 37 ], women generally report more bodily distress and more frequent somatic symptoms than men, and depressive and anxiety disorders are more prevalent in women as well. Studies on somatic symptoms have mentioned the influence of educational level [ 10 , 13 , 14 , 22 ], but the importance of this factor remains unexplored. Although the findings of this study suggest a possible association between these variables (gender and educational level) and the FSS, it must be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the published research on this field has reported high correlations between FSS and depressive and anxiety disorders [ 12 , 13 , 14 , 15 , 16 ], pointing out as the main reason for the assessment of psychopathological symptoms being included when measuring the severity of somatic symptoms [ 17 , 18 , 19 , 20 ]. In addition to the relationship of FSS with mental disorders, studies have shown a significant influence of sociodemographic characteristics on the severity of the condition presented by individuals with FSS [ 10 , 21 , 22 ]. However, the results on this relationship are controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MUPS patients are often considered "difficult" by General practitioners. These patients usually present with many bizarre symptoms, which forces the physician to advise multiple investigations and seek referral services early in outpatient visits [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…This multidimensional nature of somatization is reflected in existing literature, as etiological studies of all presentations of the condition have broadly considered the interdependent role of personality, cognitive, psychodynamic and social and cultural factors in shaping the symptom experience (Kirmayer & Looper, 2006). Furthermore, the epidemiology of somatization differs as per age (Hilderink et al, 2013), sex (D'Souza & Hooten, 2019), educational background, marital and socioeconomic status (Baitha et al, 2020) and even manifestation (Escobar et al 2010). The conceptualizations of the construct itself tend to vary in eastern and western cultures (Parker et al, 2001a) such that in India, somatization is generally viewed as a culturally sanctioned idiom of distress (Desai & Chaturvedi, 2017).…”
mentioning
confidence: 99%